2017
DOI: 10.1021/acscatal.7b00388
|View full text |Cite
|
Sign up to set email alerts
|

Direct Synthesis of Hydrogen Peroxide from Hydrogen and Oxygen over Mesoporous Silica-Shell-Coated, Palladium-Nanocrystal-Grafted SiO2 Nanobeads

Abstract: Many studies have been conducted on core–shell structured nanocatalysts thanks to their high thermal and physical stability. However, for a typical core–shell structure, shell thickness and pore size that affect mass transfer through the shell are difficult to control. Herein, we synthesized a different type of core–shell catalyst, in which a mesoporous silica shell encapsulates the Pd-nanocrystals-grafted-SiO2 nanobeads. With the preparation method introduced, we successfully controlled the thickness of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(25 citation statements)
references
References 58 publications
0
25
0
Order By: Relevance
“…The shortcomings of the anthraquinone process can be overcome via the direct synthesis of H 2 O 2 from H 2 and O 2 , outlined in Figure , which provides a greener, more atom efficient process for H 2 O 2 generation and has the potential to be adopted at point of use. In particular, Pd‐based catalysts have been demonstrated to offer high activity towards the direct synthesis of H 2 O 2 . However, catalytic selectivity is often a concern and requires the use of halide and strong acid additives to inhibit H 2 O 2 degradation and the production of H 2 O via decomposition and hydrogenation pathways, both of which are more thermodynamically favourable than the formation of H 2 O 2 .…”
Section: Introductionmentioning
confidence: 99%
“…The shortcomings of the anthraquinone process can be overcome via the direct synthesis of H 2 O 2 from H 2 and O 2 , outlined in Figure , which provides a greener, more atom efficient process for H 2 O 2 generation and has the potential to be adopted at point of use. In particular, Pd‐based catalysts have been demonstrated to offer high activity towards the direct synthesis of H 2 O 2 . However, catalytic selectivity is often a concern and requires the use of halide and strong acid additives to inhibit H 2 O 2 degradation and the production of H 2 O via decomposition and hydrogenation pathways, both of which are more thermodynamically favourable than the formation of H 2 O 2 .…”
Section: Introductionmentioning
confidence: 99%
“…The passivation procedure was applied and the setup was thoroughly cleaned once it had been found that catalyst traces were present after the coating experiments (Table 1, Exp.-Nr. : [29][30][31][32][33][34][35][36][37]. Experiments affected by catalyst traces are obviously not shown in this work and are neither part of the experimental discussion.…”
Section: Methodsmentioning
confidence: 81%
“…Lastly, structural modifications of the support material are known to influence catalyst performance as well. Pd/TiO 2 modified with heterogeneous carbon [34] and core-shell structured Pd/SiO 2 with a microporous Si shell on silica beads [35] showed an increased catalytic performance with decreased adsorption of H 2 O 2 .…”
Section: Introductionmentioning
confidence: 99%
“…[60][61][62] Thus, extensive efforts have been devoted to achieve direct synthesis of H 2 O 2 from H 2 and O 2 using variousc atalysts, enabling efficient and on-site H 2 O 2 production, which not only significantly reduces the cost for H 2 O 2 synthesis, transport, storage, and handling, but also facilitates the subsequento xidationr eactions. [60][61][62][63][64][65][66][67][68][69][70] However,agas mixture of H 2 andO 2 has potentiale xplosion risk. It is highly desired to produce H 2 O 2 from H 2 Oa nd O 2 without using H 2 .…”
Section: Introductionmentioning
confidence: 99%